The Importance of Bıologıcal Dıversıty in Economıc Terms - Gerard J. Mangone (International Journal of Science and Society, 2021)
The environmental movement, which started in the 1970s, had been changed to the view of biological resources. It is understood that Biological resources are not enough resources as economical, which is perceived as inexhaustible goods till this period. Therefore it has come into question the conservation and sustainability of these resources. When to be included in the economical politics, biological diversity started to be taken measures about ensuring sustainable use is a guarantee of continuity of human life's continuity and biosphere. Protection measures can be taken as an essential condition of success is the possible loss of biodiversity and biodiversity of the economic importance, and it is possible to know the value. The potential loss of biological diversity, as it is ecological processes, can cause loss of power that is immendable and in economic and socio-cultural processes. In this context, primarily the goods and services provided by these services' biological diversity to identify and ecological, economic and socio-cultural processes need to display the possible values. This is possible by combining ecological functions of the financial position in sustainable economic policies under the same roof. However, in this case, efficient resource use can be assured of effective policies. Especially in some countries, which have rich biodiversity, in making a rational choice, in developing countries' resources, it needs to display the economic importance that goods and services provider of biological diversity. İn this study, it has determined that goods and services provided of biological diversity and have been trying to put the biodiversity and loss of biodiversity of the economic importance were assessed with the ecological processes.